Promoting international cooperation on the International Lunar Research Station: Inspiration from the ITER. (February 2023) - Xu, Fengna; Ou, Jun
Abstract: With the deepening of space exploration, the moon has significant value for scientific research. However, because of such research's costs and risks, international cooperation will be critical for the future lunar exploration. In 2021, China and Russia jointly initiated the International Lunar Research Station (ILRS) project and released the Guide for Partnership (V1.0). However, the basic regulatory framework for creating the ILRS project is not yet in place, posing a challenge to pursuing this complex and technically ambitious endeavor. The paradigm of international cooperation that was the International Thermonuclear Experimental Reactor (ITER) project set a good example of how scientific research could transcend geographic boundaries. This paper examines the ITER Agreement, the constitutive agreement of the ITER, and analyzes the successful experience of large-scale international cooperation on a complex scientific project. Then, in view of the characteristics of the ILRS project and the existing space law, the main elements of a regulatory framework for international cooperation on this project are proposed, which follows the ITER Agreement closely. The paper concludes that such a regulatory framework for international cooperation on the ILRS project may contribute to the peaceful exploration and use of the moon, thus promoting the well-being and interests of humankind. Highlights: The moon has significant value for scientific research. International cooperation will be critical for the future lunar exploration. A regulatory framework for the International Lunar Research Station (ILRS) is not in place. The paradigm of international cooperation on the ITER set a good example. The main elements of a regulatory framework for the ILRS are proposed.